2017
DOI: 10.17352/jgro.000030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Infusion of Granulocyte Colony Stimulating Factor on IVF Outcomes in Infertile Women

Abstract: Objective: The primary goal of this study was to assess the G-CSF effects on IVF outcomes in women with normal endometrial thickness. Patients and Methods:This was a randomized controlled study performed at Assisted Reproductive Techniques Center of Ain Shams University Maternity Hospital, over a 2-year period, between Jan 2014 and Jan 2016, and included 60 infertile women with normal endometrial thickness. Women were scheduled for IVF and randomized into two groups. Exclusion criteria were positive history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…MedCalc ® version 12.3.0.0 (Ostend, Belgium) was used in sample size calculations, statistical calculator based on 95% confidence interval, and power of the study at 80% with α error 5%. A previous study (Mostafa & Farid, 2017) reported clinical pregnancies in 22% of the patients given G-CSF and in 16% of the women in the control group, with a significant difference between the two groups (p-value <0.05). Based on the findings published in this study, the minimum sample size calculated to find such difference was 95.…”
Section: Sample Size Calculationmentioning
confidence: 76%
“…MedCalc ® version 12.3.0.0 (Ostend, Belgium) was used in sample size calculations, statistical calculator based on 95% confidence interval, and power of the study at 80% with α error 5%. A previous study (Mostafa & Farid, 2017) reported clinical pregnancies in 22% of the patients given G-CSF and in 16% of the women in the control group, with a significant difference between the two groups (p-value <0.05). Based on the findings published in this study, the minimum sample size calculated to find such difference was 95.…”
Section: Sample Size Calculationmentioning
confidence: 76%